Effects of a peer-led educational intervention based on the theory of planned behavior on alcohol use intention and behavior among secondary school students in Northeast Ethiopia - Yitbarek Wasihun; Morankar Sudhakar Narayan; Eshetu Girma (PLoS ONE, 2026)
Background Adolescent alcohol use is a growing public health concern in Ethiopia. Theory-driven, peer-led educational interventions may modify psychosocial determinants of drinking behavior. This study assessed the effectiveness of a peer-led educational intervention grounded in the Theory of Planned Behavior (TPB) in changing alcohol-related intentions and self-reported alcohol consumption among secondary school students in Dessie and Kombolcha town, Northeast Ethiopia, high adolescent school enrollment. Methods A quasi-experimental pretest-post test control study with class-level allocation was conducted in four public secondary schools in Northeast Ethiopia between February and June 2021. A total of 1,496 students aged 15–24 years were assigned to intervention (n = 748) or control (n = 748) groups. Full randomization at the individual student level was not feasible due to the risk of contamination within classrooms, so intact classes were used as units of allocation. The intervention consisted of four 60-minute peer-led sessions targeting TPB constructs and knowledge. Outcomes were assessed at baseline and three months post-intervention using validated self-administered questionnaires. Generalized estimating equations (GEE) accounting for class-level clustering were used to estimate adjusted effects. Results At three months, intervention students demonstrated significantly higher alcohol-related knowledge (β = 4.76, 95% CI: 4.27–5.25), lower behavioral intention to drink (β = −1.03, 95% CI: −1.30 to −0.76), and reduced self-reported current alcohol use (adjusted OR = 0.58, 95% CI: 0.44–0.72; p < 0.001) compared with controls. Significant improvements were also observed in attitudes, subjective norms, and perceived behavioral control. Conclusions The TPB-based peer-led school intervention was associated with short-term improvements in alcohol-related knowledge, psychosocial determinants, and reductions in intention and self-reported alcohol use. These findings are limited by the three-month follow-up, self-reported outcomes, and urban-only study sites. Randomized controlled trials with longer follow-up across diverse settings are warranted to assess sustainability and causal effects.